(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2018)
Medication error is one of the healthcare challenges which effects 10 percent of individuals around the world and medication management is a complicated process including multiple activities. One of these activities is medication intake which is handled by patients. Technologies, specifically mobile health technologies are potential solutions for medication error and medication nonadherence. Moreover, designers need to be familiar with system requirements which are inducted from user’s goals. Therefore the interaction design method is an appropriate method to design the medication management systems. According to the importance of medication management, the researches performed a review study about mHealth-based medication management systems in order to extract the system requirements and usable technologies in this area to help the designers to design efficient system.